The incidence of Reproductive Disorders in Dairy Cows under Smallholder Farms - Muhammad Yusuf; Abdul Latief Toleng; Djoni Prawira Rahardja; Su Thanh Long (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2020)
The objective of this study was to know the incidence of reproductive disorders in smallholder dairy farms. The study was conducted in 12 small dairy farms in Enrekang Regency, Indonesia. A total of 80 dairy Holstein Friesian cattle consisted of 51 dairy cows and 29 dairy heifers were used in the present study. All dairy cattle at each farm were housed in tie-stall barns. Reproductive examination was conducted to determine the incidence of reproductive disorders both vaginoscopy and palpation per rectum. The incidence of reproductive disorders was 30.0%; 31.0% in dairy heifers and 29.4% in dairy cows. Uterine infection was the most reproductive disorder suffered to the dairy cattle (12.5%), followed by inactive ovaries and cyst (10% and 5%, respectively). The dairy cattle suffered from reproductive disorders increased the likelihood to mate (artificial insemination; AI) greater than three times as well as to become pregnant. In the population of dairy cattle, 48% AI was conducted greater than three times. The pregnancy rate for the dairy cattle suffered from reproductive disorders was only 20%, with interval from calving to conception was 550 days in average. It can be concluded that high incidence of reproductive disorders in smallholder dairy farms. The occurrence of reproductive disorders decreased the reproductive performance of the dairy cattle in smallholder farms.